(untitled) (Hoboken, New Jersey, 2015)
Provides the fundamentals, technologies, and best practices in designing, constructing and managing mission critical, energy efficient data centers
Trung tâm dữ liệu
Keywords: Thiết kế và xây dựng,Bộ phận xử lý dữ liệu điện tử,Design and construction,Electronic data processing departments